Pengaruh Perilaku Kewirausahaan dan Lingkungan Keluarga Terhadap Keberhasilan Usaha Kuliner Kecamatan Medan Johor - Tambunan, Kezia Emmayanti; Aramita, Finta (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study was to determine whether entrepreneurial behavior has a significant effect on business success, to determine whether the family environment has a significant effect on business success and to determine whether entrepreneurial behavior and family environment have a significant effect on the success of culinary businesses in Medan Johor District. The population in this study was 47 culinary MSMEs in Medan Johor District. The sample in the study was 47 culinary MSMEs in Medan Johor District which was carried out using saturated samples. The data collection technique used in this study was carried out by distributing questionnaires. The analysis technique used in this study was multiple linear regression, partial test (t-test), simultaneous significance test (F-test) and coefficient of determination. The results of the study showed that there was an influence of entrepreneurial behavior on business success, there was an influence of the family environment on business success and there was an influence of entrepreneurial behavior and family environment on business success in MSMEs in Medan Johor District.